UNVEILING STUDENTS' ENGAGING EXPERIENCES WITH WHATSAPP IN ENHANCING ENGLISH SPEAKING SKILLS - Fauzi, Andi Rizki (Politeknik Negeri Jakarta, 2024)
This research aims to investigate the experiences of students in using WhatsApp for English language learning, particularly in the context of speaking. The study was conducted with 34 third-semester students from the STIPARY Tourism Academy of Yogyakarta. A mixed-method approach was employed, wherein the researcher utilized a questionnaire to gather quantitative data. Additionally, qualitative data were obtained through in-depth interviews with 9 randomly selected students and observations during the use of WhatsApp in speaking lessons. The students' experiences with WhatsApp were assessed over 3 months. The questionnaire underwent validity and reliability testing, focusing on the student's learning experiences in speaking from three aspects: linguistic (vocabulary, pronunciation, grammar, and fluency), psychological (motivation and self-confidence), and environmental (flexible learning, collaborative learning, access to learning materials, and challenges related to negative reactions from the surrounding environment during speaking practice). Data analysis results indicated that students perceived positive experiences regarding the use of WhatsApp in speaking, addressing the aforementioned aspects. However, further research with a broader sample size is warranted to validate these findings